EQ-4 Potential Vector in Equistrian Diseases Free Zone, Jakarta International Equistrian Park Pulomas Indonesia - Upik Kesumawati Hadi; Susi Soviana; . Sugiarto; Isna Lailatur Rohmah; Fahmi Khairi (Hemera Zoa, 2018)
In preparation of the equestrian competitions of the 18th Asian Games Jakarta, Indonesia has to set up an Equine Disease Free Zone (EDFZ) with a core zone at the Jakarta International Equistrian Park Pulomas (JIEPP) venue and a surrounding surveillance zone covering the area of DKI Jakarta and a protection zone covering Greater Jakarta (DGLAHS 2018). EDFZ is a horse disease free zone defined by OIE to hold horse racing competitions at the Asian Games and is only valid temporarily. Vector surveillance is one of the biosecurity requirement in the monitoring of progress of EDFZ in control and eradication for various diseases, such as mosquito borne diseases. There are several mosquito-borne viral diseases that cause varying levels of morbidity and mortality in humans and animals that can have substantial welfare and economic ramifications (Durand et al. 2013). Periodic collection of local mosquito species is essential to inform vector control strategies and track their impact on mosquito borne diseases (Chapman et al. 2016). The study was done to describe the potential vector species in core zone, the habitats, the fluctuation dynamics and the potential disease spread. The result of this study will benefit in contributing the develompment of strategies to monitor and manage the risk.